THE SIGNIFICANCE OF FUNCTIONAL AND ETIOLOGICAL DIAGNOSTIC FOR TREATMENT STRATEGY DECISION IN PATIENTS WITH DILATED CARDIOMYOPATHY - Yu. V. Frolova (Российский кардиологический журнал, 2014)
Aim. To evaluate the role and importance of the functional and etiological diagnosis in determining the surgical treatment of patients with dilated cardiomyopathy (DCM). Material and methods. We examined 156 patients (40 women and 116 men) with dilated cardiomyopathy (DCM) aged 18-75 (average age — 48.8+/- 11.4) for the period from 2008 to 2013. The history of the disease averaging 54.8 +/-5.7 months; 15 (10%) of patients were in functional class II, 49 (31%) — in class III, 92 (59%) — in class IV. Results. The mean end-diastolic LV diameter was 7.45+/-1.2 cm, ejection fraction — 26.7+/- 2.1%. We performed blood PCR analysis in all the patients: Genome of herpes simplex virus type 1 was reported in 14 (9%), type 2 — in 7 (4%), type 6 — in 12 (8%) patients; of cytomegalovirus — in 20 (13%), of Epstein-Barr virus — in 24 (15%), of parvovirus B19 — in 29 (19%); we performed morphological study of the myocardium to detect cardiotropic viruses genome in 66 patients: genome of herpes simplex virus type 6 was found in 13 (23%), of cytomegalovirus — in 7 (12%), of Epstein-Barr virus — in 9 (15%), of parvovirus B19 — in 24 (42%). Depending on etiological factors, initial functional state of the patient as well as the severity of valvular regurgitation and the degree of interventricular dyssynchrony, 24 patients were implanted with cardioverter defibrillator (ICD) and 38 patients — with cardiac resynchronization therapy with cardioverter defibrillator function (CRT-D): in total, 62 patients with DCM; 24 patients underwent organ conserving reverse cardiac remodeling; orthotopic heart transplantation was performed in 13 patients; conservative treatment group consisted of 57 patients with DCM for whom surgical treatment was not recommended or impossible at the moment of the examination. Conclusion. These data indicate that application of complex etiological and functional diagnostics allows us not only to make nosological diagnosis of patients with DCM but also to determine the type of treatment and prognosis.